Transparency of the Distribution of Santana BUMDes Funds in Rajadatu Village, Cineam District, Tasikmalaya Regency in the Perspective of Sharia Financial Management - Aristhantia, Isti Tresna; Hardjanto, Tio Dwi; Prihandayani, Riska Dwi; Mujib, Haqibul; Nabila, Wildan; Ahmadi, Riki (Khidmat, 2024)
An examination of Sharia Financial Management is crucial for educating individuals about the need of transparency in reporting and distributing funds from Village-Owned Enterprises in Rajadatu Village, Cineam District, Tasikmalaya Regency. The research methodology employed is descriptive qualitative field research, utilizing primary data sources. The findings from the Economic Seminar Activity Program conducted on August 26, 2023, indicate that BUMDes Santana has distributed monies to Rajadatu Village Owned Enterprises in a transparent manner. BUMDes Santana faced fluctuations in community engagement, leading to the failure of planned initiatives by the village government. Additionally, there was a shortage of personnel resources, particularly individuals with IT proficiency or managerial experience. It is advisable for the management to require all administrators and business actors to create written regulations, such as a structured framework that outlines the implementation of Islamic principles, specifically the principles of honesty, justice, and balance. These principles should be applied in accordance with the established rules, and any violations should be met with appropriate sanctions. Ensure the BUMDes structure is properly managed by utilizing the available human resources in line with their expertise, and implement the applicable management regulations.